Energy-Aware Low-Power CMOS LNA with Process-Variations Management - Jorge Luis González; Robson Luiz Moreno; Juan Carlos Cruz; Diego Vázquez (Active and Passive Electronic Components)
A reconfigurable low-noise amplifier (LNA) with digitally controllable gain and power consumption is presented. This architecture allows increasing power consumption only when required, that is, to improve LNA’s radiofrequency performance at extreme communication-channel conditions and/or to counteract the effect of process, voltage, and temperature variations. The proposed design leads to significant power saving when a relaxed operation is acceptable. The LNA is implemented in a 130 nm 1.2 V CMOS technology for a 2.4 GHz IEEE-802.15.4 application. Simulated LNA performance (taking into account the worst cases under process variations) is comparable to recently published works.